Esensi Pemaknaan Kata “Demokratis” Dalam Pemilihan Kepala Daerah Di Indoneisa Pasca Perubahan UUD NRI 1945 - Daud, Annisa Nur Ftriyani; Dungga, Wenny Almoravid; Mandjo, Julius T. (CV. ITTC INDONESIA, 2022)
Democracy is the ideal of the Indonesian people. One way to realize this democracy is through the election of regional heads directly or through DPRD, of course, it must also be based on democratic regional head elections as mandated by Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia. Democratic regional head elections also have procedures and stages based on popular sovereignty and democracy in question. Interpreting the word democratic in Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia does not necessarily see that regional head elections must be direct regional head elections and vice versa. To interpret democratic regional head elections one must know, study and analyze 2 models of regional head elections in Indonesia in order to obtain accurate data to be able to find out what kind of democracy is desired by the constitution of the Republic of Indonesia. The method used in this writing is library research, namely by collecting materials from books, papers, laws and regulations and Internet media as well as the results of other scientific writings that are closely related to the aims of writing this thesis. The results of this study explain the meaning of democracy in article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia, to better understand the democratic regional head elections mandated by the constitution to be carried out by the Indonesian government and people. Democracy in the laws and regulations that have been in force in Indonesia